2020
DOI: 10.1158/2326-6066.cir-19-0517
|View full text |Cite
|
Sign up to set email alerts
|

Combined CD44- and CD25-Targeted Near-Infrared Photoimmunotherapy Selectively Kills Cancer and Regulatory T Cells in Syngeneic Mouse Cancer Models

Abstract: Near-infrared photoimmunotherapy (NIR-PIT) is a newly developed and selective cancer treatment that induces necrotic and immunogenic cell death and utilizes a mAb conjugated to a photo-absorber dye, IR700DX, activated by NIR light. Although CD44 is a surface cancer marker associated with drug resistance, anti-CD44-IR700 NIR-PIT results in inhibited cell growth and prolonged survival in multiple tumor types. Meanwhile, CD25targeted NIR-PIT has been reported to achieve selective and local depletion of FOXP3 þ CD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…Near-infrared photoimmunotherapy can concurrently destroy multiple cell types if multiple APCs are injected. For example, combined CD44-and CD25-targeted NIR-PIT has been shown to kill both cancer cells and Tregs, resulting in greater immune activation and inhibition of tumor growth than either therapy alone [13]. However, CD44 is expressed on both cancer cells and immune cells [5], thus, CD44-targeted NIR-PIT might reduce antitumor immunity and is, therefore, not an ideal model to analyze the additional effect of CD25-targeted NIR-PIT.…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared photoimmunotherapy can concurrently destroy multiple cell types if multiple APCs are injected. For example, combined CD44-and CD25-targeted NIR-PIT has been shown to kill both cancer cells and Tregs, resulting in greater immune activation and inhibition of tumor growth than either therapy alone [13]. However, CD44 is expressed on both cancer cells and immune cells [5], thus, CD44-targeted NIR-PIT might reduce antitumor immunity and is, therefore, not an ideal model to analyze the additional effect of CD25-targeted NIR-PIT.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed MOC1 tumor has low and more heterogeneous CD44 expression and CD44-targeted NIR-PIT was less effective against this type of tumor [ 13 ]. The NIR-PIT regimen and imaging protocol are depicted in Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%
“…This report represents an extension of previous studies which attempt to augment the immune response initiated by NIR-PIT. For instance, a previous study demonstrated that the combination of CD44-targeted NIR-PIT and either immune checkpoint blockade or Treg-targeted NIR-PIT showed inconsistent therapeutic efficacy among these three tumor models [ 13 , 14 , 24 ]. CD44-targeted NIR-PIT in combination with other therapies showed promising results in MC38-luc and LL/2 but was less effective against MOC1 tumor which has low CD44 expression and fewer CD44 positive tumor cells compared to MC38-luc and LL/2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44 is a well-known marker of cancer stem cells [ 8 ] and anti-CD44-mAb-IR700 NIR-PIT induces effective tumor killing in CD44-expressing syngeneic mouse models [ 9 , 10 , 11 ]. Recently, the combination of CD44-targeted NIR-PIT and programmed cell death protein 1 (PD-1) immune checkpoint blockade was reported to induce massive tumor cell death and innate priming of polyclonal, cancer antigen-specific T-cell responses in several cancer models, resulting in complete tumor rejection and the generation of immunologic memory [ 10 ].…”
Section: Introductionmentioning
confidence: 99%